Male infertility risk and plasma lipidome: a Mendelian randomization study - Yang, Yang; Xue, Xinyu; Zhou, Jun; Qiu, Zerui; Wang, Biao; Ou, Guangyang; Zhou, Qing (Frontiers in Endocrinology, 2024)
In recent years, the decline in sperm quality in men has become a global trend. There is a close relationship between sperm quality and pregnancy outcome. There is a large body of literature supporting the role of plasma lipidome in male infertility, while the complex mechanisms between them and male infertility are still less clear. Systematic study of the causal relationship between plasma lipidome and MI can help to provide new therapeutic ideas and targets for male infertility.In this study, we used a two-sample Mendelian randomization analysis based on Genome-wide association studies pooled data of 179 causal relationships between plasma lipidome and male infertility. We used employed the inverse variance weighted method as the main analysis to assess causality between exposure and outcome, in addition to MR-Egger, Weighted median as complementary methods, and tests for multiplicity and heterogeneity.We identified 13 plasma lipidome comprising 4 types of plasma lipidome that were associated with male infertility. Among these, 9 plasma lipidome were found to be protective factors, while 4 were risk factors. Notably, the largest proportion of these plasma lipidome were triglyceride types, with Sphingomyelin (d40:1) exhibiting the strongest association with male infertility. CONCLUSION: These findings contribute to the current better understanding of male infertility and provide new perspectives on the underlying etiology of male infertility as well as prevention and treatment strategies. In addition, clinical trial validation is needed to assess the potential of these plasma lipidome as biomarkers.